2021
DOI: 10.21203/rs.3.rs-809653/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Exosomes Derived from Bone Marrow Mesenchymal Stem Cell Preconditioned by Low-Intensity Pulsed Ultrasound Stimulation Promote Bone-Tendon Interface Fibrocartilage Regeneration and Ameliorate Rotator Cuff Fatty Infiltration

Abstract: Fibrovascular scar healing of bone-tendon interface (BTI) instead of functional fibrocartilage regeneration is the main concern associated with unsatisfactory prognosis in rotator cuff repair. Mesenchymal stem cells exosomes have been reported to be a new promising cell-free approach for rotator cuff healing. Whereas, controvercies abound in whether exosomes of native MSCs alone can effectively induce chondrogenesis. In this study, we aimed to explore the effect of Exosomes derived from low-intensity pulsed ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Forty-five articles were included after screening and all of them were case–control studies [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 ]. Another article was included by searching the references of the included articles and review articles related to the topic [ 85 ]. Finally, 46 studies were included for synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty-five articles were included after screening and all of them were case–control studies [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 ]. Another article was included by searching the references of the included articles and review articles related to the topic [ 85 ]. Finally, 46 studies were included for synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…All studies had a low risk of baseline characteristics under selection bias, random outcome assessment under detection bias, attrition bias, reporting bias, and other biases [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. All studies reported baseline characteristics of the animals used which included the species, age and gender of the animals, and the outcomes were randomly assessed [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Feng et al discovered that exosomes derived from genetically modified Scleraxis-overexpressing PDGFRα(+) BMMSCs delivered miR-6924–5p to prevent osteoclast formation during tendon–bone healing and enhance the biomechanical strength of the TBI [ 89 ]. A recent study conducted by Wu et al found that exosomes derived from low-intensity pulsed ultrasound stimulation (LIPUS)-preconditioned bone marrow mesenchymal stem cells (LIPUS-BMSC-Exos) could improve fibrocartilage regeneration at the tendon–bone interface and decrease supraspinatus fatty infiltration in a murine RC repair model by promoting BMSC chondrogenesis and anti-adipogenesis, which was primarily by delivering miR-140 [ 90 ]. Similarly, Z. Li et al demonstrated that BMSC-derived exosomes (BMSC-Exos) overexpressing miR-23a-3p could promote M1 macrophage to M2 macrophage polarization, reduce the early inflammatory reaction at the tendon–bone interface, and promote early healing after ACL reconstruction [ 91 ].…”
Section: Current Progress In the Application Of Exosomes To Tbi Injuriesmentioning
confidence: 99%